Microsoft Office PowerPoint 2003 step by step (Microsoft Office step by step)
Summary: With this book you will: master the tools for transforming your ideas into winning presentations ; use ready-made design templates or create your own look ; make your point with compelling charts, diagrams, graphics, text, and hyperlinks to Web content ; keep it dynamic - animate your slides, insert sounds and movies, and create transitions ; and deliver your presentation in person, over the Web, or on CD.